ANALISIS ANGGARAN SEBAGAI MANAJEMEN PENGENDALIAN BIAYA PRODUKSI PT. BARAWAJA - Nurfadila nurfadila; Muhammad Reza Ramdani (AKUNTANSI DEWANTARA, 2021)
Budget in a company is a tool of assist management for implementation, planning, coordination, supervision functions and also as a work guideline in running the company for predetermined purposes. The research objective is an analyze and describe the function of the budget as a means of controlling production costs. descriptive quantitative approach to research by collecting data documentation through operational report. The analytical method used analysis of variance operational costs. Research findings explain PT. Barawaja regarding the production budget as a control tool has not been implemented optimally.